RESPON EVALUATIF PETANI TERHADAP KELOMPOK TANI DALAM PERSPEKTIF KONDISI SOSIAL EKONOMI - Johny A. Koylal (Partner, 2009)
valuative Response Farmer Towards Group Farmer In Perspective Condition Social Economy. The aim of this research of answering the problem as follows: 1) how the farmer's attitude towards the farmer's group? And 2) Whether the social factor economics had relations that were real with the farmer's attitude towards the farmer's group? This research was carried out in the Maulafa Subdistrict, Kupang, NTT for eight months, beginning with March 2008 up to October 2008.This research used the descriptive and technical method the data collection used the technique survey. The taking method of the sample was carried out in stages: 1) the determination of the example district deliberately (Purposive Sampling) that is the Kolhua District, Fatukoa District and Sikumana District and 2) the determination of the example farmer (the respondent) that  was carried out Reasonably Random Sampling totalling 15% from all the members of the farmer's group in all the example districts. The total respondent who was used in the research was 36 farmers.The data that was received was tabulated in accordance with the need of the analysis.  To  know the  attitude  and  the  perception of  the  farmer  towards  the farmer's group, the data was analysed by using descriptive statistics, whereas to know whether social factors economics had real relations with the farmer's attitude towards the group of the data farmer was analysed by using the Rank Spearman correlation.Results of the research showed that: 1) generally the member of the farmer's group in the Maulafa Subdistrict had a hesitant attitude about the farmer's group with the score of the attitude in general 35.56; and 2) the social factor economics that had real relations with the farmer's attitude towards the farmer's group was the number of securities of the family. Therefore, the social factor economics that could be used to forecast the farmer's attitude towards the farmer's group was the factor of the number of securities of the family.Keywords:.